2022
DOI: 10.1002/pa.2809
|View full text |Cite
|
Sign up to set email alerts
|

Market‐focused flexibility and innovative performance in public healthcare: Evidence from India

Abstract: The healthcare sector is increasingly facing changing demand patterns and escalating pressures for innovative services during the COVID-19 pandemic. Market-focused flexibility refers to the capabilities of adaptation and facilitating the innovative performance of the firm. Accepting the overall role of innovation in COVID-19 response, this study aims to explore how public healthcare organizations exhibit marketfocused flexibility to introduce new and innovative services. This study conducts an exploratory case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 98 publications
(229 reference statements)
0
6
0
Order By: Relevance
“…As we progressed, we defined and refined the identified themes by carefully analyzing the collated data extracts to capture the essence of each theme, and we may also uncover sub-themes to provide a clearer structure. Lastly, we presented the entire data analysis procedure and its findings in a comprehensive report (Kumar, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…As we progressed, we defined and refined the identified themes by carefully analyzing the collated data extracts to capture the essence of each theme, and we may also uncover sub-themes to provide a clearer structure. Lastly, we presented the entire data analysis procedure and its findings in a comprehensive report (Kumar, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 Exhaustive list of purchasing manager's competencies capability of market orientation (Barton, 1992;Amit and Schoemaker,1993;Teece et al, 1997) during their relationships with suppliers. As has been explained by authors studying other domains and industries, market orientation can be identified as an adoptive, flexible and dynamic capability, which positively impacts firm's innovative performance (Kohli and Jaworski, 1990;Javalgi, et al, 2005;Yadav et al, 2007;Kumar, 2020Kumar, , 2022Cataltepe et al, 2022;Muneeb et al, 2023).…”
Section: Knowledge Gap and Research Objectivementioning
confidence: 98%
“…Because the present environment and modern society are considered inconsistent, uncertain, complex and unpredictable, so in such case, the SF is deemed an important factor that helps the organizations (e.g. health sector; Kumar, 2022) to deal with today’s complex and uncertain business environments (Brozovic, 2018; Haarhaus and Liening, 2020). For instance, Bera et al (2022) examined the flexibility in the health sector via reducing patients’ waiting time to deal with uncertain environments.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…For instance, Bera et al (2022) examined the flexibility in the health sector via reducing patients’ waiting time to deal with uncertain environments. Kumar (2022) determined the role of market-based flexibility to bring innovation performance in public health services.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation